Role of Body Weight on Reproductive and Physiological Traits in Japanese Quail Layers (Coturnix japonica) - Arora, Kashmiri L.; Samples, Oreta (International Journal of Poultry Science, 2011)
The Japanese quail is a popular laboratory animal for scientific research. Its continued characterization is essential for attaining accurate and reliable results. This includes refining genetic and environmental variables that could affect its use in developmental biology, reproduction, physiology, nutrition, endocrinology and toxicology. The role of body weight as a means of assessing reproductive and physiological traits is presented here. Two groups of random bred Japanese quail layers of 240-days of age having a well-established production and fertility records but differing in body weights were used in the project. One group of birds (n = 10) weighed 120-130 grams (lighter birds) and the second group (n = 10) weighed 150-160 grams (heavier birds). The heavier birds had significantly higher weights of ovaries and oviducts as well as larger yellow-yolk containing ovarian follicles (p0.05). Conversely, there was an increase in packed cell volume, plasma proteins and decrease in blood sugar levels (p